Impact of response shift effects in the assessment of self-reported depression during treatment: Insights from a rTMS versus Venlafaxine randomized controlled trial. (April 2023) - Bulteau, Samuel; Blanchin, Myriam; Pere, Morgane; Poulet, Emmanuel; Brunelin, Jérôme; Sauvaget, Anne; Sébille, Véronique
Abstract: Purpose: Patient-Reported Outcomes are essential to properly assess treatment effectiveness in randomized clinical trial (RCT) for Major Depressive Disorder (MDD). MDD self-assessment may vary over time depending on change in the meaning of patients' self-evaluation of depression, i.e. Response Shift (RS). Our aim was to investigate RS and its impact on different depression domains in a clinical trial comparing rTMS versus Venlafaxine. Methods: The occurrence and type of RS was determined using Structural Equation Modeling applied to change over time in 3 domains (Sad Mood, Performance Impairment, Negative Self-Reference) of the short-form Beck Depression Inventory (BDI-13) in a secondary analysis of a RCT on 170 patients with MDD treated by rTMS, venlafaxine or both. Results: RS was evidenced in the venlafaxine group in the Negative Self-Reference and Sad Mood domains. Conclusion: RS effects differed between treatment arms in self-reported depression domains in patients with MDD. Ignoring RS would have led to a slight underestimation of depression improvement, depending on treatment group. Further investigations of RS and advancing new methods are needed to better inform decision making based on Patient-Reported Outcomes.